Dalea carthagenensis una nueva fuente de compuestos antioxidantes: Identificación de polifenoles y actividad antifúngica contra Rhizopus stolonifer en yaca: Extract with antifungal activity - Calderón-Santoyo, Montserrat; González-Gutiérrez, Katia Nayeli; Vilchis-Gómez, Doane Santalucia; Dominguez-Ruvalcaba, Jesus Emmanuel; Ragazzo-Sanchez, Juan Arturo (Revista Bio Ciencias, 2024)
The soft rot caused by Rhizopus stolonifer is the most important disease in jackfruits. Currently, the control of this phytopathogen is achieved with toxic fungicides. Due to this, the control of R. stolonifer is sought through natural alternatives such as plant extracts. This study aimed to identify the compounds in Dalea carthagenensis extract and evaluate its antifungal potential against important postharvest phytopathogens. The antioxidant activity of the extract and the in vitro activity against Penicillium italicum, Colletotrichum gloeosporioides, and R. stolonifer were evaluated. The chemical compounds were identified by HPLC-UV-Vis and the in vivo antifungal activity was assessed against R. stolonifer in jackfruit. The extract presented an antioxidant activity of 48.34 ± 1.3 mg TE/g dw and a total phenolic content of 52.23 ± 0.57 mg GAE/g dw. P. italicum, C. gloeosporioides, and R. stolonifer were inhibited between 11.50-55.6%, 22.16-53.88%, and 27.46-79.71%, respectively. The most sensitive fungus was R. stolonifer with a minimum inhibitory concentration of 11.08 mg/mL. D. carthagenensis extract reduced the severity of soft rot by 59% in jackfruits and gallic acid and vanillin were the main compounds identified. In conclusion, D. carthagenensis extract is a promising alternative for managing soft rot disease in jackfruit at postharvest stage. The extract offers an eco-friendly control solution for jackfruit growers.